Enhancing Financial Reporting Accuracy through Zahir Accounting Software Implementation: A Case Study of PT Kuat - Turiman Turiman (SEAN Institute, 2026)
This study aims to analyze the implementation of Zahir Accounting Version 6 in improving financial reporting accuracy and financial management effectiveness at PT Kuat, an Event Organizer and MICE company in Jakarta. The company previously utilized a manual accounting system that frequently caused recording errors, delays in financial reporting, difficulties in transaction monitoring, and inadequate financial data storage. This research employed a qualitative approach using a case study method. Data collection techniques included observation, interviews, and documentation involving financial transaction records and company financial statements. The implementation process consisted of software installation, company database setup, opening balance input, transaction recording, and automated financial statement generation. The findings indicate that Zahir Accounting significantly improved transaction recording efficiency, reduced human error, accelerated financial reporting processes, and strengthened financial data security through computerized data storage systems. Furthermore, the software contributed to improving the accuracy and reliability of financial information used for managerial decision-making. Therefore, the implementation of computerized accounting systems supports digital financial transformation within service-based companies.